Training day on mini-sett yam production - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2021)
In Jamaica the larger seed yams which are at least one and a half pounds in weight are ideally suited for the export market which can now be presented with uncut yams which have a longer shelf life ans lower post-harvest weight loss.